An Analysis of Derivational Suffixes Found in Reading Texts of English Textbook - Safitri Haryati Putri; Hasan Basri; Darmawan Darmawan; Anshari Syafar; Abdul Kamaruddin; Aminah (Jurnal Kreatif Online, 2021)
This research aimed to analyze the function of derivational suffixes found in reading texts of English textbook for the eleventh-grade students of senior high school. The methodology used descriptive content analysis. The samples were selected in which words containing derivational suffixes found in reading texts of English textbook. Data were collected through data reduction, data display and concluding. The researcher found that there were four basics of types and functions of derivational suffixes. The types of derivational suffixes are nominal, verbal, adjectival, and adverbial suffixes. The most frequently suffixes used in English textbook is the nominal suffix –ing as a noun marker and followed by adverbial suffix –ly as an adverb marker. The researcher concludes that the functions of derivational suffixes are to create new a word by adding the suffixes to the end of root word by following the pattern: noun-forming to create noun, verb-forming to create verb, adjective-forming to create adjective, and adverb-forming to create adverb.